Exploring The Unconscious Motives in The Short Story the Kite by Somerset Maugham - Malik, Sana; Sadaf , Aliha; Akram Khan, Muhammad (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
The article focuses on the influence of the Freudian psychoanalytic theories and the in the riveting writings of William Somerset Maugham. This article has narrowed down its focus on the only one enthralling short story by Maugham, namely ''The Kite''. Somerset Maugham and Sigmund Freud's lives intersected in the early years of the twenty-first century. They were both fascinated by human relationships and the building blocks of human bonds. This study was qualitative descriptive. The theory adopted for analyzing the selected text was the Freud approach to the issue as a psychoanalyst and clinician. Simultaneously, Maugham delved deep into the psyche and behavior of human beings he met, watched, and interacted with. This article aims to critically evaluate the compelling themes and motives of Maugham's short stories and to establish the ascendancy of the theories of psychoanalysis as propounded by Freud in them.